Imaging and surgical planning for perihilar cholangiocarcinoma. (12th February 2014) - Endo, Itaru; Matsuyama, Ryusei; Mori, Ryutaro; Taniguchi, Koichi; Kumamoto, Takafumi; Takeda, Kazuhisa; Tanaka, Kuniya; Köhn, Alexander; Schenk, Andrea
Abstract Recent advances in multidetector computed tomography (MDCT) offer several benefits for management of perihilar tumors. Resection planning for perihilar cholangiocarcinoma should consider two factors: safety and curability. Recognition of individual anatomic variations is particularly important for avoiding intraoperative injury. In particular, hepatic arterial variations often restrict resection procedures. Extent of both longitudinal and vertical invasion by biliary tumors can be estimated from multiplanar reconstruction (MPR) images. Longitudinal extent of resection can be planned based on two anatomic landmarks, the U point and the P point, readily identifiable in preoperative 3‐dimensional (3D) images and by intraoperative inspection. Concerning vertical invasion, when direct vascular invasion is suspected from a finding of attachment of tumor and vessels such as portal veins and/or hepatic arteries without a thin low‐density plane of separation shown by MPR, these vessels should be resected en bloc with the tumor. Surgical team members can plan and simulate details of vascular resection and reconstruction using 3D images. Reduced operative morbidity and increased R0 resection rates are expected because of better planning of procedures. These techniques soon may increase long‐term survival for patients with perihilar cholangiocarcinoma.